Mapping Potential Commercialization of Research Results Through Valuation and Technology Readiness Levels - Octavia, Ade; Ekasari, Novita; Surya Hartati, Dwi; Habibi, Akhmad (Dinasti Publisher, 2024)
Downstreaming the results of ’lecturers’ research is a strategic activity to improve the performance of a higher education institution (HEI) which requires research on mapping the commercialization potential. This research aims to understand the role of research centres in the commercialization process and increasing start-ups at one Indonesian university, Universitas Jambi (UNJA). Besides, this research maps the potential for commercialization assessed from the valuation system and technology readiness levels (TRL). This research is important for achieving the institution vision of